KEEFEKTIFAN MODEL PEMBELAJARAN GROUP INVESTIGATION TERHADAP HASIL BELAJAR IPS (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2016)
This study aims to know the effectiveness of learning group investigation model for learning result of IPS (Social Sciences) in grade V at SDN Gugus Melati in Semarang. This research is a kind of quasi experimental research. The technique of sample collection use cluster random sampling technique. The subject of research is grade V SDN Kalipancur 2 as control class with 45 students and Grade V SDN Purwoyoso 4 as experiment class with 39 students. The data collection techniques in research are observation, documentation and test. Data shows student’s learning outcome that posttest average experiment class lager than control class. Posttest mean of the experiment group is 82,18 and posttest mean of the control class is 70,11. Test result-t showing value thitung (6,458) ttabel (1,980) means that students learning result use Group Investigation model is large than direct instruction learning model.The conclusion of this research is Group Investigation model more effective than direct instruction learning model.